Decision‐making determinants for breast reconstruction in women over 65 years old. Issue 6 (10th July 2019) - Quemener, Julie; Wallet, Jennifer; Boulanger, Loic; Hannebicque, Karine; Chauvet, Marie‐Pierre; Régis, Claudia
Abstract: Despite the positive effects that breast reconstruction (BR) has on quality of life, access to it remains limited for older women. The aim of this study was to identify decision‐making determinants for BR in women over 65 years old, using a specifically designed questionnaire. We included in a case‐control study 134 patients treated by mastectomy for breast cancer with or without BR in a cancer center performing BR. We showed higher motivation scores and quality of delivered information in the BR group. Surgeons are a key in convincing elderly patients that their age should no longer be an obstacle to BR.